Recurrent infections in partial complement factor I deficiency: evaluation of three generations of a Brazilian family - Grumach, Anete; Leitão, M F; Arruk, V G; Kirschfink, Michael; Condino-Neto, A (Clinical & experimental immunology, 2006)
We report here on the evaluation of a factor I-deficient Brazilian family (three generations, 39 members) with strong consanguinity. The complete factor I-deficient patients (n = 3) presented recurrent respiratory infections, skin infections and meningitis; one of them died after sepsis. They presented an impaired total haemolytic activity (CH50), low C3, low factor H and undetectable C3dg/C3d. Partial factor I deficiency was detected in 16 family members (normal low cut-off value was 25 µg/ml). Respiratory infections were the most common clinical occurrence among partial factor I-deficient relatives. Two of them were submitted to nephrectomy following recurrent urinary tract infections. An additional two heterozygous relatives presented with arthritis and rheumatic fever. Apparently, patients with partial factor I deficiency are also at higher risk for recurrent infections. Vaccination against capsulated bacteria and the eventual use of prophylactic antibiotics should be considered individually in this patient group.